(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1918)
Britain is remarkable in Ptolemy’s work for the amount of distortion and much analysis is required to understand how his errors arose, and from what material he was building. The author considers, absolute positions, coasting distances, inland distances in England, the Lowlands and the Highlands to try to ascertain what date Ptolemy used, and how he worked.